2015
DOI: 10.1111/jep.12448
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility criteria in systematic reviews published in prominent medical journals: a methodological review

Abstract: The quality of reviews in these leading medical journals was high; however, there were issues that reduce the clarity and replicability of the review process. As well as providing a useful checklist, this methodological review informs the continued development of standards for systematic reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…excluding protocol violators or individuals that were lost for follow-up). In a recent studies, McCrae et al [56] found that study eligibility criteria for primary study inclusion, search data restrictions and use of unpublished data was often not properly documented in published reviews. Further, Akl et al [57] demonstrated that most systematic reviews do not check for, or account for, missing data.…”
Section: Resultsmentioning
confidence: 99%
“…excluding protocol violators or individuals that were lost for follow-up). In a recent studies, McCrae et al [56] found that study eligibility criteria for primary study inclusion, search data restrictions and use of unpublished data was often not properly documented in published reviews. Further, Akl et al [57] demonstrated that most systematic reviews do not check for, or account for, missing data.…”
Section: Resultsmentioning
confidence: 99%
“…That way, the readers will understand that these studies were not missed in the search. 31 Ideally, the decision about eligibility of studies should be made while investigators are blinded to the results of the study, the source of publication, and the institution where the study was performed. This is recommended because investigators selecting studies may be more likely to include publications that report results consistent with their preconceived ideas and may be more likely to choose studies published in prestigious journals or conducted by specific investigators.…”
Section: Search Strategy: Study Eligibilitymentioning
confidence: 99%